On Vague Cosets and Vague Normal Subgroups - Tarun Kumar (International Journal of Intelligent Systems and Applications in Engineering, 2023)
In the present paper, some basic concepts of vague sets and vague groups together with the concepts of vague left and right cosets of a vague group were studied. To more appropriately introduce the vague normal subgroup, we made use of the feature of vague sets and, as a result, some characterizations of vague groups. We also gave some basic concepts related to vague cosets and on behalf of these concepts we proved some classical group theorems and we generalized some new theorems and their proofs on fuzzy coset and fuzzy normal subgroups to the vague coset and vague normal subgroups. We also discussed some important properties.